Zircon U–Pb geochronology and Nd isotope systematics of the Guro Suite granitoids, Mozambique: Implications for Neoproterozoic crust reworking events. (December 2018) - Manjate, Vicente Albino; Tassinari, Colombo Celso Gaeta
Abstract: The Zambezi belt is the eastern segment of a Pan-African (∼850-450Ma) orogenic belt system in southern Africa which also comprises the Lufilian arc and the Damara belt. Although for some authors the Zambezi belt is a suture zone along which a major Proterozoic ocean basin between the Congo and Zimbabwean cratons has closed, this study argue that the Zambezi belt originates from an aborted intracontinental rift. New SHRIMP U–Pb zircon geochronology, whole rock Sm–Nd isotopes, and geochemical data are reported for the charnockites, granite-gneisses, and TTGs of the Guro Suite. The results are used to check the period of magmatism and crustal growth in the Guro suite, evaluate the involvement of older continental material in the crustal growth, and to clarify the regional crustal evolution models. The zircon U-Pb data record extensional detachment faulting at c. 870–830 Ma followed by protolithic crystallization, which occurred at c. 835–822 Ma and a Pan-African tectono-metamorphic event at 576–540 Ma. The Guro Suite is bimodal consisting of mafic and ultramafic lenses, blocks and boudins hosted by granite-gneisses, charnockites, and TTG. The Guro Suite granitoids are of A-Type within-plate magmatism associated with an aborted intracontinental rift. The Nd model ages (1.32–1.94 Ga) of the Guro Suite rocks are significantly older than their protolithic crystallization ages (835–822 Ma) determined by U–Pb in zircon, suggesting a significant input of pre-Neoproterozoic crustal material in the Zambezi belt. Graphical abstract: